Contribution to the phylogeography of the nose-horned viper (Vipera ammodytes, Linnaeus, 1758) in the Central Balkan Peninsula - Čubrić, Tijana; Stamenković, Gorana; Ilić, Marija; Crnobrnja-Isailović, Jelka (Archives of Biological Sciences, 2019)
Paper description: Seven main genetic clades have been previously recognized within Vipera ammodytes but the distribution boundaries between those groups have not been clearly defined. Our study used sequences of the 16S rRNA mitochondrial DNA gene to determine the molecular phylogenetic position of boundary area populations of the nose-horned viper in Serbia and adjacent regions using novel samples. We recognized the presence of three main Vipera ammodytes genetic clades in Serbia instead of two previously identified in the literature. Our findings contribute to the knowledge of genetic diversity in Serbia and further delimit the geographical distributions of Vipera ammodytes clades in the Central Balkan Peninsula. Abstract: Seven genetic clades have been recognized within the species Vipera ammodytes (nose-horned viper); however, the precise phylogenetic position of many Balkan populations is unknown. We used Bayesian analysis of the mtDNA sequences from the 16S rRNA mtDNA gene obtained from 47 individuals (26 novel samples sequenced in this study and 21 sequences available from GenBank). Our results show that sampled nose-horned vipers from localities in Serbia are clustered within three clades: the northeastern (23 individuals), the northwestern (two individuals) and the southeastern (one individual). Results revealed an overlapping distribution of the northeastern and the northwestern clades in two populations. We have revealed that the northeastern clade extends further south than previously suggested, to the Ohrid/Prespa lakes in North Macedonia. Our findings contribute to the knowledge of the genetic diversity of this species in Serbia and help to clarify the geographical distributions of mtDNA-defined clades. https://doi.org/10.2298/ABS181020028C Received: October 20, 2018; Revised: March 11, 2019; Accepted: April 17, 2019; Published online: April 24, 2019 How to cite this article: Čubrić T, Stamenković G, Ilić M, Crnobrnja-Isailović J. Contribution to the phylogeography of the nose-horned viper (Vipera ammodytes, Linnaeus, 1758) in the central Balkan peninsula. Arch Biol Sci. 2019;71(3):463-8.